2012
DOI: 10.1111/j.1749-6632.2011.06431.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and conservation biology of avian malaria

Abstract: Avian malaria is a worldwide mosquito-borne disease caused by Plasmodium parasites. These parasites occur in many avian species but primarily affect passerine birds that have not evolved with the parasite. Host pathogenicity, fitness, and population impacts are poorly understood. In contrast to continental species, introduced avian malaria poses a substantial threat to naive birds on Hawaii, the Galapagos, and other archipelagoes. In Hawaii, transmission is maintained by susceptible native birds, competence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
268
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(275 citation statements)
references
References 128 publications
(376 reference statements)
3
268
0
4
Order By: Relevance
“…Similar results have been demonstrated for avian malaria, with deforestation producing variable prevalence patterns at both local and regional scales (see Sehgal 2010, LaPointe et al 2012). For example, recent studies in Africa by Bonneaud et al (2009) and Loiseau et al (2010) found higher Plasmodium prevalence in birds inhabiting pristine forests, whereas Chasar et al (2009) revealed one parasite species was more abundant in disturbed sites and another more so in pristine sites.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…Similar results have been demonstrated for avian malaria, with deforestation producing variable prevalence patterns at both local and regional scales (see Sehgal 2010, LaPointe et al 2012). For example, recent studies in Africa by Bonneaud et al (2009) and Loiseau et al (2010) found higher Plasmodium prevalence in birds inhabiting pristine forests, whereas Chasar et al (2009) revealed one parasite species was more abundant in disturbed sites and another more so in pristine sites.…”
Section: Introductionsupporting
confidence: 68%
“…However, this model is likely not applicable to continental ecosystems due to the introduced vector-parasite and naïve host system, and the Hawaiian situation is unique in that there were no bloodsucking insects prior to the accidental introduction of mosquitoes by humans (Waldbauer 2012). Nonetheless, there is a concern that other island ecosystems with high numbers of endemic birds (most notably New Zealand and the Galapagos) could be similarly affected by the interaction of exotic mosquitoes, anthropogenic environmental change and avian malaria (Derraik and Slaney 2007;LaPointe et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in attempting to explore the viability of translocation of forest bird species across the Hawaiian archipelago, we did not focus our efforts on modeling the distribution of disease and mosquitoes themselves. Besides the general lack of spatial data on the disease and vector, modeling either of these distributions would not address the differential tolerance of forest bird species to disease nor the differential environmental requirements between vector and disease (LaPointe et al., 2012). Nevertheless, because the ongoing and projected range contractions for these forest bird species are strongly related to a warming‐related shift upslope of avian malaria and its vector, it is important to consider how successful efforts to limit the spread of the disease or vector would impact our findings.…”
Section: Discussionmentioning
confidence: 99%